Bisnis Informasi Lowongan Kerja: Sebuah Komodifikasi di Portal Media Online dan Jejaring Sosial - Qholiva Yuni Fadilla (UMSU, 2020)
The information society makes the production, processing, distribution and consumption of information the primary economic and social activity. This makes information as one of the main commodities in the information society market industry. LokerJogja.ID as an online media portal and with its social media network makes job content as a marketable commodity and is considered to be able to attract the attention of the public. This study identifies and criticizes how LokerJogja.ID offers commodities in the form of job content to be of appropriate use value. By using a critical paradigm, this study uses virtual ethnography method. Data collected documentation through online media portals and social media networks used by LokerJogja.ID. Then, the findings are analyzed through collection, reduction, and presented in a qualitative-descriptive. Based on the analysis of researchers, online media portals and social networks are only used as a 'container' for profit, that is, by utilizing audiences and content that is sufficiently distributed from job openers. Not only modifying job content as something of exchange value, but LokerJogja.ID has exploited the audience. This relates to the number of audiences as followers and visitors of the online media portal and social network LokerJogja.ID which can affect the profitability of the job content platform.